Test no estresante como predictor de complicaciones neonatales en gestantes con pre-eclampsia, Iquitos 2019 al 2020 - Inuma Tafur, Elizabeth Lucero (2023)
Objective: To determine if the non-stress test predicts neonatal complications (low Apgar score, prematurity, low birth weight, neonatal sepsis, need for admission to the neonatal intensive care unit NICU, prolonged hospital stay, and meconium amniotic fluid), of pregnant women with Pre-eclampsia at the Regional Hospital of Loreto, 2019 to 2020. Methodology: This research was observational, analytical, with a cross-sectional design, where we worked with a sample of 80 pregnant women diagnosed with Preeclampsia who underwent a Non-stress test until the last 15 days before the arrest. The study variables were adverse perinatal outcomes (low Apgar, neonatal sepsis, prematurity, low birth weight, NICU admission, prolonged hospital stay, perinatal death, need for mechanical ventilation and presence of meconium amniotic fluid. For bivariate analysis and calculation of strength of association or inferential analysis was performed through the calculation of Chi square, Fisher's exact test, with a confidence level of 95% (p < 0.05) and the prevalence ratio with its respective confidence interval. The diagnostic values or predictive capacity and the safety of the diagnostic test will be calculated using the values of sensitivity, specificity, positive predictive value and negative predictive value. Results: Of a total of 80 pregnant women with preeclampsia, 12% of the NST studies were non-reactive; The non-stress test was associated with the presence of low Apgar scores, neonatal sepsis, prolonged hospital stay, prematurity, and admission to the NICU. In addition, the non-stress test has a high specificity and positive predictive value, so if a pregnant woman presents a NST Reactive test, she has a high probability that the newborn will not present any adverse perinatal outcome. Conclusions: the non-stress test is a good predictor of adverse perinatal outcomes, especially due to its high rate of specificity and negative predictive value.